2013
DOI: 10.1101/gad.222174.113
|View full text |Cite|
|
Sign up to set email alerts
|

H3.3 actively marks enhancers and primes gene transcription via opening higher-ordered chromatin

Abstract: The histone variants H3.3 and H2A.Z have recently emerged as two of the most important features in transcriptional regulation, the molecular mechanism of which still remains poorly understood. In this study, we investigated the regulation of H3.3 and H2A.Z on chromatin dynamics during transcriptional activation. Our in vitro biophysical and biochemical investigation showed that H2A.Z promoted chromatin compaction and repressed transcriptional activity. Surprisingly, with only four to five amino acid difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
220
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(231 citation statements)
references
References 49 publications
8
220
0
3
Order By: Relevance
“…H3.3 normally is enriched in active genes and in regulatory regions (35). In fact, H3.3-containing regions display a looser and more open chromatin structure (35,36). Consistent with the partial reduction in the level of histones and the increased level of the A B open-chromatin-specific H3.3, we observed that chromatin was more accessible to MNase I in SLBP-silenced cells (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…H3.3 normally is enriched in active genes and in regulatory regions (35). In fact, H3.3-containing regions display a looser and more open chromatin structure (35,36). Consistent with the partial reduction in the level of histones and the increased level of the A B open-chromatin-specific H3.3, we observed that chromatin was more accessible to MNase I in SLBP-silenced cells (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…However, the levels of the histone variant H3.3 increased strongly in SLBP-silenced cells. H3.3 normally is enriched in active genes and in regulatory regions (35). In fact, H3.3-containing regions display a looser and more open chromatin structure (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Second, while the majority of eukaryotes express distinct histone H3 variants for replication-coupled (RC) (designated histone H3.1 and H3.2 in humans) and replicationindependent (RI) (designated histone H3.3 in humans) histone deposition, S. cerevisiae has retained a histone H3.3-like variant for both pathways. The amino acid differences between RC-and RI-specific H3 variants are proposed to restrict the histones to their requisite deposition pathways (Szenker et al 2011), but these variants also directly alter chromatin structure in vitro (Thakar et al 2009;Chen et al 2013). This together with the previously established link between H3.3 deposition and active transcription in metazoans (Waterborg 1990;Johnson et al 2004;McKittrick et al 2004;Chow et al 2005;Mito et al 2005) has led to speculation that yeasts have retained H3.3 due to its ability to promote an open chromatin conformation.…”
mentioning
confidence: 99%
“…Consistently, H3.3 has been found at gene bodies and promoters of transcriptionally active genes as well as gene regulatory elements, such as enhancers (1,4,5). More recently, it has been shown that the H3.3-containing nucleosomes are compromised in their ability to form compact structure in vitro and that the H3.3 genomic distribution correlates well with DNase I-sensitive regions, suggesting a preferential association with open chromatin environment in vivo (6). Interestingly, H3.3 has also been found at pericentromeric and telomeric regions, where its deposition is largely dependent on the DAXX/ATRX chaperone system; however, the function of H3.3 at these regions remains unclear (7).…”
mentioning
confidence: 61%
“…In addition, H3.3 has also been suggested to mark active chromatin (4,6). Interestingly and perhaps somewhat counterintuitively, the H3.3K36me3 reader BS69 primarily suppresses gene expression through the mechanisms discussed in BS69 Suppresses Transcription Elongation and Promotes Intron Retention.…”
Section: Bs69 Suppresses Transcription Elongation and Promotes Intronmentioning
confidence: 99%